2004
DOI: 10.5194/angeo-22-4243-2004
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the dayside reconnection rate during an interval of due northward interplanetary magnetic field

Abstract: Abstract. This study presents, for the first time, detailed spatiotemporal measurements of the reconnection electric field in the Northern Hemisphere ionosphere during an extended interval of northward interplanetary magnetic field. Global convection mapping using the SuperDARN HF radar network provides global estimates of the convection electric field in the northern polar ionosphere. These are combined with measurements of the ionospheric footprint of the reconnection X-line to determine the spatiotemporal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 51 publications
9
73
0
Order By: Relevance
“…The square symbols represent individual reconnection rate measurements and the bold line (shaded region) represents a running median (quartile range) of those measurements a minimum total reconnection rate of *150 kWb/s, and dividing by the separatrix length at the magnetopause gives an average reconnection rate there of *0.6 Wb/s/km, comparable with independent in-situ spacecraft estimates for the same event (Phan et al 2000). This study was complemented by a similar analysis of the reconnection rate during an interval of steady, due northward IMF (Chisham et al 2004b). The ionospheric projection of the magnetopause reconnection rate determined by Chisham et al (2004b) is summarized in Fig.…”
Section: Reconnection Rate Measurementsmentioning
confidence: 48%
See 2 more Smart Citations
“…The square symbols represent individual reconnection rate measurements and the bold line (shaded region) represents a running median (quartile range) of those measurements a minimum total reconnection rate of *150 kWb/s, and dividing by the separatrix length at the magnetopause gives an average reconnection rate there of *0.6 Wb/s/km, comparable with independent in-situ spacecraft estimates for the same event (Phan et al 2000). This study was complemented by a similar analysis of the reconnection rate during an interval of steady, due northward IMF (Chisham et al 2004b). The ionospheric projection of the magnetopause reconnection rate determined by Chisham et al (2004b) is summarized in Fig.…”
Section: Reconnection Rate Measurementsmentioning
confidence: 48%
“…(a) The reconnection rate variation during an interval of due southward IMF from 1330 to 1400 UT on February 11, 1998 (from Pinnock et al 2003). (b) The reconnection rate variation during an interval of due northward IMF from 1440 to 1520 UT on November 11, 1998 (from Chisham et al 2004b). The square symbols represent individual reconnection rate measurements and the bold line (shaded region) represents a running median (quartile range) of those measurements a minimum total reconnection rate of *150 kWb/s, and dividing by the separatrix length at the magnetopause gives an average reconnection rate there of *0.6 Wb/s/km, comparable with independent in-situ spacecraft estimates for the same event (Phan et al 2000).…”
Section: Reconnection Rate Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the event studied here, however, the IMF B X was still significantly smaller than the component in the Y-Z plane, so the axial tilt of the Earth was the dominant effect on magnetospheric configuration. Chisham et al [2004] examined a similar event to the present study, where the IMF B X was negative, but comparable in magnitude to the IMF B Z , leading to enhanced convection in the northern hemisphere. Further, Burke et al [1979] also found it difficult to observe reverse convection at all in the summer months, as did the reverse convection potential saturation study done by Sundberg et al [2009].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Several techniques have been considered, based on observations of the auroral emissions (Blanchard et al, 1995;Wild et al, 2004;Hubert et al, 2006a;Boakes et al, 2008), in situ particle detection (Newell et al, 1991;Blanchard et al, 1997), analysis of radar backscatter from the moving ionospheric plasma (Milan et al 2003, and references therein; Chisham et al, 2005), or a combination of in situ particle measurements and radar backscatter analysis (Chisham et al, 2004). Estimates of the electron temperature were also used by Østgaard et al (2005) and Aikio et al (2006) to determine the location of the polar cap boundary.…”
Section: Introductionmentioning
confidence: 99%